2008
DOI: 10.1111/j.1745-7254.2008.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Felodipine attenuates vascular inflammation in a fructose-induced rat model of metabolic syndrome via the inhibition of NF-κB activation1

Abstract: Aim: Metabolic syndrome is associated with an increased incidence of atherosclerosis. Clinical studies have shown that calcium channel blockers (CCB) inhibit the progression of atherosclerosis. However, the underlying mechanism is unclear. We investigated the inhibitory effect of felodipine on adhesion molecular expression and macrophage infiltration in the aorta of high fructose-fed rats (FFR). Methods: Male Wistar rats were given 10% fructose in drinking water. After 32 weeks of high fructose feeding, they w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Since we have previously demonstrated that different stimuli are able to up-regulate TF expression via NF-jB [20,21] and given the property of fructose to induce gene target expression through NF-jB activation [24], we investigated whether fructose-mediated TF up-regulation was determined by NF-jB activation. Thus, we analyzed NF-jB activity in HUVEC cells transfected with a plasmid containing a luciferase reporter gene downstream the promoter region of immunoglobulin j light chain responsive to NF-jB activity and incubated them with fructose.…”
Section: Effects Of Fructose On Nf-jb Activationmentioning
confidence: 99%
“…Since we have previously demonstrated that different stimuli are able to up-regulate TF expression via NF-jB [20,21] and given the property of fructose to induce gene target expression through NF-jB activation [24], we investigated whether fructose-mediated TF up-regulation was determined by NF-jB activation. Thus, we analyzed NF-jB activity in HUVEC cells transfected with a plasmid containing a luciferase reporter gene downstream the promoter region of immunoglobulin j light chain responsive to NF-jB activity and incubated them with fructose.…”
Section: Effects Of Fructose On Nf-jb Activationmentioning
confidence: 99%
“…20 Our study demonstrates that a high-fructose diet can enhance vascular inflammation, which plays a role in vascular injury and ultimately in hypertension. 5 Using Wistar rats fed 10% fructose in drinking water for 38 weeks, Tan et al 40 …”
Section: Discussionmentioning
confidence: 99%
“…Using Wistar rats fed 10% fructose in drinking water for 38 weeks, Tan et al 40 showed increased expression of adhesion molecules vascular cell adhesion molecule 1 and intercellular adhesion molecule 1, as well as infiltration of monocyte/ macrophages in the aortic wall. Our results have demonstrated increased expression of vascular cell adhesion molecule 1 and platelet endothelial cell adhesion molecule 1 in the aorta of rats fed a high-fructose diet for 5 weeks.…”
mentioning
confidence: 99%
“…Immunohistochemistry analysis for Cx43 was performed in tissue samples from LA as described previously [16], using mouse monoclonal anti-Cx43 (BD Biosciences). Histopathological slides were analyzed by use of a computer-assisted morphometric analysis system (Image-Pro Plus 5.0).…”
Section: Methodsmentioning
confidence: 99%